2014
DOI: 10.1002/anie.201402363
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Cell Chemical Proteomics with an Activity‐Based Probe: Identification of Low‐Copy Membrane Proteins on Primary Neurons

Abstract: We propose a novel single-cell chemical proteomics (SCCP) strategy to profile low-abundance membrane proteins in single cells. In this approach, the membrane protein GB1 and its splicing variants were targeted on cultured cell lines and primary neurons using a specifically designed activity-based probe. The functionally labeled single cells were encapsulated in individual buffer droplets on a PDMS microwell array, and were further picked up one at a time and loaded into a capillary electrophoresis system for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…Of note, for CGP7930 there is an apparent controversy between our data where both GB1 and GB2 TMD are required to observe an agonist effect, while Binet et al, 2004 found GB2 TMD alone was sufficient. It might be due to the endogenous expression of the GB1 subunit that may exist in some cell lines including the HEK293 cells used in both studies ( Xu et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, for CGP7930 there is an apparent controversy between our data where both GB1 and GB2 TMD are required to observe an agonist effect, while Binet et al, 2004 found GB2 TMD alone was sufficient. It might be due to the endogenous expression of the GB1 subunit that may exist in some cell lines including the HEK293 cells used in both studies ( Xu et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…developed a novel single‐cell chemical proteomics strategy to profile low‐abundance membrane proteins in single cells. [ 47 ] Shi et al. built a special LIF with a fluorescent probe to quantify low copy number intracellular proteins in a single cell.…”
Section: Targeted Proteins Analysis Approachesmentioning
confidence: 99%
“…Xu et al developed a novel single-cell chemical proteomics strategy to profile low-abundance membrane proteins in single cells. [47] Shi et al built a special LIF with a fluorescent probe to quantify low copy number intracellular proteins in a single cell. [48] However, due to the vulnerability to the adsorption of proteins on the capillary wall, the detection stability is always a big challenge to the capillary-based separation method, bringing difficulties in practical application.…”
Section: Capillary Electrophoresis-laser-induced Fluorescence Detectionmentioning
confidence: 99%
“…A chemical cytometry-based on microfluidics capillary electrophoresis technology was used for single-cell chemical proteomics (SCCP) to recognize proteins present on the individual primary neuron membrane. A functional single-neuron was isolated from a mouse and injected into a capillary for generating capillary electrophoresis-laser-induced fluorescence to study receptor protein, labeled by activity-based probes [ 90 ]. The electropherogram results conclude the heterogeneous expression of GB1 probably owing to the presence of two important G-protein (GB1) variant splices (GB1a and GB1b, in CNS) or precise post-translational alterations.…”
Section: Microfluidics-based Single-neuron Omicsmentioning
confidence: 99%